Cooperatives and the Sustainable Development Goals: contributions in practice - Arzadun, Paula; Rosatelli, Paola (Cooperativismo & Desarrollo, 2025)
Purpose. This article examines the contributions of cooperative organizations to advancing the implementation of the Sustainable Development Goals (SDGs). It seeks to provide a comprehensive, multi-scalar perspective that highlights the ways in which cooperatives generate social, economic, and environmental value while embodying principles of solidarity, democracy, and sustainability. Topics. The study addresses three interconnected levels: (1) the global and regional scale, through platforms and frameworks that promote advocacy, reporting, and visibility of cooperative contributions to the SDGs; (2) the national level, where apex organizations and large cooperative enterprises play key roles in policy dialogue, representation, and strategic alignment with sustainable development agendas; and (3) the local level, where grassroots cooperatives directly impact their communities through inclusive economic practices, social innovation, and environmental stewardship. Development. Drawing on secondary data, institutional reports, and illustrative case studies, the article analyzes how cooperatives operationalize sustainable development in practice. It examines mechanisms of accountability, such as CoopImpacto platform, while also exploring challenges of visibility, policy integration, and financing. Besides, it emphasizes the relevance of multi-level governance and the articulation between cooperative networks and public institutions in fostering systemic change. Conclusions. Findings indicate that cooperatives are uniquely positioned to contribute to the SDGs by combining economic viability with social inclusion and ecological responsibility. Their multi-scalar presence enables them to act as bridges between local needs and global commitments, reinforcing the centrality of cooperative values in shaping just and sustainable futures. However, to maximize their impact, cooperatives require stronger support in terms of data, policy recognition, and resources for scaling their transformative practices.